РОЛЬ СТОРОЖЕВЫХ ЛИМФАТИЧЕСКИХ УЗЛОВ В СТАДИРОВАНИИ РАКА ЖЕЛУДКА. - Юсупов А.П.; Тулкинов Х.Х; Абдуллаев О.Б (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Alfraganus University г. Ташкент, Узбекистан. Abstract: Stomach cancer remains one of the leading causes of cancer mortality worldwide. Radical gastrectomy with D2 volume lymphodissection is the "gold standard" of surgical treatment, however, it is associated with a significant frequency of postoperative complications. In recent decades, the concept of sentinel lymph node biopsy (BSLU) has been actively developing as an alternative, less invasive method for staging lymphogenic metastasis. Having initially proven its effectiveness in breast cancer and melanoma, this approach is also being adapted for stomach cancer. This review analyzes modern methods for identifying sentinel nodes, their diagnostic accuracy, clinical advantages and disadvantages, and discusses the prospects for introducing BSL into routine practice for the personalized treatment of patients with early forms of stomach cancer. Special attention is paid to combined detection methods, including the radioisotope method and fluorescent navigation with indocyanine green (ICG), which demonstrate the highest accuracy. Despite the promising results, the heterogeneity of the data and the risk of false negative conclusions still limit the widespread use of the technique outside of clinical trials.